Studying the pattern modes of the optical fiber of the laser and comparing it with pattern modes of Graduated fiber in terms of the ellipse function (V) (Latakia University Journal -Basic Sciences Series, 2019)
It is well known that the work of optical fiber depends, mainly, on a principle of light engineering which is the total internal reflection, which requires that the refraction index of the medium from which the light (pulp) n1 is greater than the refraction index of the second medium (glass cover) n2 and thus n1 can be Changed in different ways, such as being fixed in all the first medium and thus we get a fiber called a leap in the index fiber, or to be changeable gradually after the point in the first medium of the center of the fiber so the fiber is called then:the fiber with a gradual refraction index. It is well known that the form of the fiber patterns depends Largely on the refraction idex of the both mediums. we are going to examine the impact of refraction  mechanism changing mechanism on the patterns of the fiber, then to compare between the patterns of the two mentioned above, in terms of the cutting function(V).